El cambio climático y la producción de alimentos de origen vegetal (The climate change and the production of foods of vegetable origin) - Carranza Araujo, Rocio Yovany (2017)
The objective of this review is to provide sufficient information to the reader on the current effects of climate change on the production of food of plant origin, so that it can raise awareness in the conservation of the environment and the mitigation of climate change. Since this environmental problem is an inescapable reality and the actions to face them are also imperative. Since in recent years it has been a real threat to the well-being of our population and its present manifestations, the same ones observed in the increase in the price of food, the availability and quality of energy and water, and Such as increased vulnerability to hydrometeorological events. That being so, we all have an obligation to protect ecosystems, as they are of great importance for biodiversity and the dampening of current and future climate changes; These ecosystems must be taken care of and used in a sustainable manner with the support of alliance civil society, public and private companies at national level, the primary objective of this work. It encourages business and personal activities to promote adaptation and mitigation to climate change, the search for energy from renewable sources and the reduction of dependence on fossil fuels, sustainable management of water resources and Food safety. The present work invites the reader to develop and strengthen local capacities to address this situation, trying to find possible solutions to climate change mitigation in the production of food of plant origin in all areas of the country